The Implementation of Health Protocols in Facing Pandemic Covid-19 at Ragunan Wildlife Park - Armaini Akhirson (Yayasan Ilomata, 2022)
This study aims to determine the health protocol for the New Normal preparation for the tourism sector in the Ragunan Wildlife Park. This research is a type of research that uses descriptive data through data collection techniques of observation, interviews, documentation and literature study. The data analysis technique used for this writing is qualitative with descriptive data analysis techniques based on the data analysis literature, data reduction, data processing and research conclusions. The results of this study indicate that the existence of this pandemic has had a major impact on the tourism sector of the Ragunan Wildlife Park. As a result, many activities cannot be carried out because this pandemic has resulted in the closure of tourist attractions and no income. However, this makes the welfare of the existing animals calmer, living like in real nature without many tourist visits. The existing animals do not lack food or medicine at all because this has received a subsidy from the DKI Jakarta Provincial Government of 70% of 100% of which 30% is income from ticket sales. The Ragunan Wildlife Park has established a health protocol that is enforced according to the government's decision, both for tourists and animals and hopes that this pandemic will end quickly and return to normal for the welfare of all.